Peningkatan Prestasi Belajar dan Sikap Kemandirian Siswa melalui Model Problem Based Learning pada Materi Operasi Hitung Perkalian Pecahan di Kelas V SD Negeri 3 Purbalingga Lor - Damayanti, Zulinda Fara; Badarudin, Badarudin (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2024)
The poor levels of student achievement and attitude towards independent learning in mathematics in fifth grade primary school inspired this study. Finding out how the problem-based learning (PBL) paradigm improves students' attitude towards independence and their mathematical learning accomplishments was the main goal of this study. There will be two iterations of this classroom action research project. Two meetings made up each cycle. There are four steps to this research: preparation, execution, monitoring, and analysis. A total of twenty-four students, twelve male and twelve female, from VB class in SD Negeri 3 Purbalingga Lor in the Purbalingga District, participated in the study. Examinations, observation sheets, and surveys were utilised as instruments for gathering data. Mathematical proficiency improved with each cycle, according to the data. Results for cycle I were 65.31 with a learning completeness rate of 52.08%, while results for cycle II were 81.35 with a rate of 81.24%. There was a 29% increase between cycles I and II. (2) The percentage of students who exhibited an attitude of independence rose from 65.5% in cycle I to 81.50% in cycle 2.